Risk Management Strategies in Financial Institutions - Yuliani (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to explore the factors that influence the effectiveness of risk management strategies in financial institutions. Through analysis of variables such as the level of risk awareness across the organization, the level of success in identifying and mitigating the impact of risks, and employee participation in the risk management process, our findings show that these factors have a significant influence on the effectiveness of risk management strategies. Financial institutions that have a strong risk culture, supported by a high level of risk awareness and open communication about risk across the organizational hierarchy, tend to be more successful in managing risk and achieving their goals. The practical implication of this research is the importance of strengthening risk culture, increasing risk awareness throughout the organization, and encouraging active employee participation in the risk management process to increase the effectiveness of risk management strategies in financial institutions.